The effects of instructions and labels on choice between environmental friendly and non-friendly products - Pedroso, Reginaldo; Coelho, Cristiano (Perspectivas em Análise do Comportamento, 2019)
This study aimed to compare the effect of instructions and the presence of the environmental certification on choices between products with and without signal of sustainable production in two experiments: 1) Price of different products (lamp, softener, sulphite paper, and bed) with environmental certifications relative to products without environmental certification, with and without pro-environmental instruction, with 24 undergraduate students; 2) Several brands of the same product (softener), with and without environmental certification, aiming to estimate if the relative price would vary according to the level of knowledge, quality and sustainability, with 12 undergraduate students. The task in both experiments was to choose one product between each pair in successive choices. In the Experiment 1, the data showed that only for the lamp the relative subjective prices with the two instructions were higher for the sustainable product. In the Experiment 2, it was observed that the higher the level of knowledge, the lower the price relative to the non-sustainable product. The absence of correlation between relative price and sustainability shows that the certification had low discriminative properties. One of the possibilities for intervening to increase pro-environmental behavior involves a set of contingencies for the individual and the companies that produce them.